PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TAI DAN STAD PADA MATERI GERAK TUMBUHAN PADA SISWA KELAS VIII SMP NEGERI 3 NAMROLE - Maria Natalia Seleky; M Nur Matdoan; Ine Arini (Program Studi Pendidikan Biologi FKIP Unpatti, 2017)
Background: The TAI (Team Assisted Individualization) model is individual assistance in the characteristic group that the responsibility is for students. Therefore students must build knowledge without accepting the finished form of the teacher. While the STAD Model (Student Team Achievement Division) is to motivate students to be able to support and help one another in mastering the abilities taught by the teacher. Method: This research was conducted on April 10, 2017 - May 10, 2017 with the research location on Junior High School 3 Namrole. To find out the difference in learning outcomes, it was analyzed using T-test analysis. Results: Through the design of quasi-experimental research shows that there are no differences in student learning outcomes taught using the TAI and STAD models, but in the TAI and STAD classes almost all students reach KKM 68. However, based on the calculation of the average (mean) and standard deviation for the class TAI 76.68 and class 75.31 so that it can be said that the TAI model is more effective than STAD. Conclusion: There is an increase in student learning outcomes after conducting the teaching and learning process by using the Team Assisted Individualization and Student Team Achievemint Devision models so that the t-test results show that thit <ttab with thit 1.023 and ttab 2.0105.